Granulocyte-macrophage colony-stimulating factor is a key mediator in inflammatory and arthritic pain. Issue 2 (24th July 2012) - Cook, Andrew D; Pobjoy, Jarrad; Sarros, Shannon; Steidl, Stefan; Dürr, Manuela; Lacey, Derek C; Hamilton, John A
Abstract : Objectives: Better therapies are needed for inflammatory pain. In arthritis the relationship between joint pain, inflammation and damage is unclear. Granulocyte-macrophage colony-stimulating factor (GM–CSF) is important for the progression of a number of inflammatory/autoimmune conditions including arthritis; clinical trials targeting its action in rheumatoid arthritis are underway. However, its contribution to inflammatory and arthritic pain is unknown. The aims of this study were to determine whether GM–CSF controls inflammatory and/or arthritic pain. Methods: A model of inflammatory pain (complete Freund's adjuvant footpad), as well as two inflammatory arthritis models, were induced in GM–CSF −/− mice and development of pain (assessment of weight distribution) and arthritic disease (histology) was assessed. Pain was further assessed in a GM–CSF-driven arthritis (methylated bovine serum albumin/GM–CSF) model and the cyclooxygenase-dependence determined using indomethacin. Results: GM–CSF was absolutely required for pain development in both the inflammatory pain and arthritis models, including for IL-1-dependent arthritic pain. Pain in a GM–CSF-driven arthritis model, but not the disease itself, was abolished by the cyclooxygenase inhibitor, indomethacin, indicating separate pathways downstream of GM–CSF for pain and arthritis control. Conclusions: GM–CSF is key to the development of inflammatory and arthritic pain, suggesting that pain alleviation could result from trials evaluating its role in inflammatory/autoimmune conditions.